Production and Characterization of Neutral and Alkaline Protease from Different Bacillus subtilis Strains - Uyar, Fikret; Baysal, Zubeyde (Asian Journal of Chemistry, 2010)
An extracellular neutral and alkaline protease from two different Bacillus subtilis strains were studied. The optimal activity occured when the pH level was 7.0 and 10.5 at a temperature of 35 and 45 ºC for neutral protease and alkaline protease, respectively. When neutral protease was stable in the temperature range 35-60 ºC, alkaline protease was found stable between 35-55 ºC for 0.5 h. Divalent cations, especially Ca2+ increased enzymes activity and were inhibited by Mn2+,Ni2+, Cu2+, Fe2+, Co2+, Cd2+ and Hg2+ for neutral protease and by Zn2+, Cd2+,Co2+, Cu2+ and Hg2+ for alkaline protease. The neutral protease was also inhibited by ethylenediaminetetraacetic acid, 1,10 phenanthroline and dithiothreitol whereas alkaline protease was inhibited with phenylmethyl-sulfonyl fluoride. The obtained Km values were 2.28 × 10-3 ± 3.65 × 10-4, 2.28 × 10-4 ± 4.21 × 10-5 and 1.70 × 10-4 ± 5.18 × 10-5 M for azocasein, BSA and casein for neutral protease, respectively. The Km values with azocasein, BSA, casein, N-suc-Ala-Ala- Ala-pNA and N-cbz-Ala-Ala-Leu-pNA were 2.02 × 10-3 ± 7.3 × 10-5, 2.13 × 10-4 ± 6.04 × 10-5, 8.75 × 10-4 ± 1.36 × 10-4, 1.71 × 10-3 ± 3.93 × 10-4 and 2.64 × 10-4 ± 4.93 × 10-5 for alkaline protease.